PENGEMBANGAN ALAT EVALUASI BERBASIS LITERASI SAINS PADA MATERI GELOMBANG DI SMAN 1 CEPIRING - Rohman, Muhammad Arif (UPEJ Unnes Physics Education Journal, 2023)
This study aims to; 1) determine the feasibility of a science literacy-based evaluation tool on the material of waves; 2) determine the results of the analysis of the science literacy profile of class XI students of SMAN 1 Cepiring on the material of waves. This research is a Research and Development (R&D) study using the Analyze, Design, Development, Implementation and Evaluation (ADDIE) Dick & Carry model. The research data were obtained from observation and tests. The test instrument consists of 35 items that were validated by two Physics Lecturers of Semarang State University and two Physics Teachers. The results of expert validation show that the test instrument is valid and feasible with a percentage of 87%. Data analysis in this study used Rasch model analysis using the Winstep application. Rasch model analysis carried out includes reliability analysis, item fit, Wright map, item measure, person fit, and person measure. The technique of analyzing science literacy ability using the percentage method. The results of this study produce a reliable test instrument with a person reliability of 0.71, item reliability of 0.91 and show that the science literacy profile of class XI students of SMAN 1 Cepiring is in the very low category with a percentage of 43.40%. Penelitian ini bertujuan untuk; 1) mengetahui kelayakan alat evaluasi berbasis literasi sains pada materi gelombang; 2) mengetahui hasil analisis profil literasi sains siswa kelas XI SMAN 1 Cepiring pada materi gelombang. Penelitian ini merupakan penelitian Research and Development (R&D) menggunakan model Analyze, Design, Development, Implementation and Evaluation (ADDIE) Dick & Carry. Data penelitian ini diperoleh dari observasi dan tes. Instrumen tes berjumlah 35 butir soal yang divalidasi oleh ahli dua Dosen Fisika Universitas Negeri Semarang dan dua Guru Fisika. Hasil validasi ahli menunjukkan bahwa instrumen tes valid dan layak dengan persentase sebesar 87%. Analisis data pada penelitian ini menggunakan analisis model Rasch menggunakan aplikasi Winstep. Analisis model Rasch yang dilakukan meliputi analisis reliabilitas, item fit, peta wright, item measure, person fit, dan person measure. Teknik analisis kemampuan literasi sains dengan menggunakan metode persentase. Hasil penelitian ini menghasilkan instrumen tes yang reliabel dengan person reliability sebesar 0,71, item reliability sebesar 0,91dan menunjukkan profil literasi sains siswa kelas XI SMAN 1 Cepiring berada dalam kategori sangat rendah dengan persentase sebesar 43,40%.